Syrian Refugees in Turkey and Integration Problem Ahead - ERDOĞDU, MUAMMER MUSTAFA (SPRINGER HEIDELBERG, 2019)
In this study, the Syrian refugees' integration problems are examined, and the main challenges such as learning the tongue, finding jobs, housing, education, and vulnerability to abuse are analyzed. Moreover, some measures for social integration were proposed. Because of the civil war that broke out in Syria in 2011, many Syrians had to leave their homes and find shelter in neighboring countries. Turkey applied an open door policy from the beginning and received an influx of Syrian refugees and asylum seekers. Turkey is now de facto home to over 3.5 million registered Syrians, along with non-registered ones. Refugee influx has initially been regarded as temporary and Syrian refugees are seen as guests. Especially after the influx in 2014-2015, however, the positive emotions began gradually fading and some started to pronounce refugees as overstaying guests. Eventually, perspectives have shifted from short-term protection and humanitarian assistance to longer-term social and economic integration of Syrian refugees. Long-term integration and settlement of the refugees necessitate a comprehensive, unified, and rigorous approach. It also requires greater cooperation between policymakers, practitioners, and civil society organizations in different areas such as employment, education, and health. In addition, it calls robust international cooperation and support.
Keywords: Syrian refugees; Integration; Turkey